Single coronary artery presenting dilated cardiomyopathy and hyperlipidemia with the SCN5A and APOA5 gene mutation: A case report and review of the literature - Hu, Xiaoxia; Kong, Jing; Niu, Tingting; Chen, Liang; Yang, Jingjing (Frontiers in Cardiovascular Medicine, 2023)
We present a 55-year-old man with chest tightness and dyspnoea after activity lasting for 2 months who was diagnosed with single coronary artery (SCA) and presented with dilated cardiomyopathy (DCM) with the c.1858C > T mutation in the SCN5A gene. The computed tomography coronary angiogram (CTCA) showed congenital absence of the right coronary artery (RCA), and the right heart was nourished by the left coronary artery branch with no apparent stenosis. Transthoracic echocardiography (TTE) revealed enlargement of the left heart and cardiomyopathy. Cardiac magnetic resonance imaging (CMR) revealed DCM. Genetic testing showed that the c.1858C > T variant of the SCN5A gene could lead to Brugada syndrome and DCM. SCA is a rare congenital anomaly of the coronary anatomy, and this case reported as SCA accompanied by DCM is even rarer. We present a rare case of a 55-year-old man with DCM with the c.1858C > T (p. Arg620Cys)/c.1008G > A (p.(Pro336=) variant of the SCN5A gene, congenital absence of RCA, and c.990_993delAACA (p. Asp332Valfs*5) variant of the APOA5 gene. To our knowledge, this is the first report of DCM combined with the SCN5A gene mutation in SCA after searching the PubMed, CNKI and Wanfang databases.